2021
DOI: 10.1002/pc.25999
|View full text |Cite
|
Sign up to set email alerts
|

Non‐isothermal crystallization kinetics of polypropylene/bamboo fiber/nano‐TiO2composites

Abstract: Non-isothermal crystallization kinetics of polypropylene/bamboo fiber/nano-TiO 2 (PP/BF/nano-TiO 2 ) composites was investigated using differential scanning calorimetric technique with various cooling rates (2.5, 5, 10, 20, and 30 C min −1 ). The influence of different loading concentration (0, 0.1, 0.4, and 0.8 wt%) of TiO 2 nanoparticles on the nucleation ability of polypropylene was evaluated. The Avrami equation, Ozawa, and Mo model were applied to describe the non-isothermal crystallization behaviors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…As small amount of nano‐TiO 2 was added, the crystallization temperature of the composites remained basically unchanged with a tiny increase in the degree of crystallinity (X c ). Here, nano‐TiO 2 played the role of heterogeneous nucleation, which increased the crystallization rate of PP phase and made it easier to form a regular crystalline structure 48,49 . The decline in the degree of crystallinity (X c ) was found when nano‐TiO 2 loading content was increased to 0.5 wt% owing to the possible agglomeration which would hinder the mobility of PP molecular chains 50 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As small amount of nano‐TiO 2 was added, the crystallization temperature of the composites remained basically unchanged with a tiny increase in the degree of crystallinity (X c ). Here, nano‐TiO 2 played the role of heterogeneous nucleation, which increased the crystallization rate of PP phase and made it easier to form a regular crystalline structure 48,49 . The decline in the degree of crystallinity (X c ) was found when nano‐TiO 2 loading content was increased to 0.5 wt% owing to the possible agglomeration which would hinder the mobility of PP molecular chains 50 …”
Section: Resultsmentioning
confidence: 99%
“…Here, nano-TiO 2 played the role of heterogeneous nucleation, which increased the crystallization rate of PP phase and made it easier to form a regular crystalline structure. 48,49 The decline in the degree of crystallinity (X c ) was found when nano-TiO 2 loading content was increased to 0.5 wt% owing to the possible agglomeration which would hinder the mobility of PP molecular chains. 50 For composites with UV-P, the crystallization and melting temperature were in the absence of regular variation, but the crystallinity of PP phase continues to decrease.…”
Section: Dsc Analysismentioning
confidence: 99%
“…[ 16–18 ] PLA is a semicrystalline polymer, and the crystallization behavior strongly influences mechanical and thermal properties. [ 19–21 ]…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29][30] The mainly is due to nanoparticles can significantly enhance the viscoelasticity and crystallization of the matrix, thereby improving the cell structure and mechanical properties of the foam. [31][32][33][34][35] Nano TiO 2 not only exhibits advantages of small particle size, large specific surface area and high surface activity, but also has strong stability, photocatalytic activity and UV shielding ability, [36][37][38] due to amphoteric oxide, a differentiated traditional nanoparticle filler generate a great expectation for foamed WPC. However, to the author's knowledge, there have been very few studies of the injection molding of WPC using nano TiO 2 particles to improve the foaming behavior and mechanical performances of PP-based WPC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the introduction of nanoparticles, such as talc, clay, fabric, and carbon and organic fibrils, can improve the melt strength, generate more foaming nucleation sites, and reduce cell collapse and coalescence by the wood flour (WF) to produce a microcellular‐foamed PP‐based WPC composed of uniform dense cells and enhanced mechanical and foaming performances 25–30 . The mainly is due to nanoparticles can significantly enhance the viscoelasticity and crystallization of the matrix, thereby improving the cell structure and mechanical properties of the foam 31–35 . Nano TiO 2 not only exhibits advantages of small particle size, large specific surface area and high surface activity, but also has strong stability, photocatalytic activity and UV shielding ability, 36–38 due to amphoteric oxide, a differentiated traditional nanoparticle filler generate a great expectation for foamed WPC.…”
Section: Introductionmentioning
confidence: 99%